(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. This article, which based on the theoretical justification of scientific literature, presents a theoretical analysis of the problem of person’s self-education. There was determined the conceptual categorical apparatus and also some essential features of the process of self-education were revealed. The structure and dynamics of self-education’s process in the context of the category of self-awareness are revealed. The role of self-knowledge, self-regulation, self-alignment, self-esteem in the direction of positive personality transformations is especially emphasized. It was established that the processes of self-education and self-regulation are conscious practical actions which are aimed at a more complete realization by a human of himself as a person. Prospects for further research are outlined.